Angiogenic patterning by STEEL, an endothelial-enriched long noncoding RNA - Man, H S Jeffrey; Sukumar, Aravin N; Lam, Gabrielle C; Turgeon, Paul J; Yan, Matthew S; Ku, Kyung Ha; Dubinsky, Michelle K; Ho, J J David; Wang, Jenny Jing; Das, Sunit; Mitchell, Nora; Oettgen, Peter; et al. (Proceedings of the National Academy of Sciences - PNAS, 2018)
Endothelial cell (EC)-enriched protein coding genes, such as endothelial nitric oxide synthase (eNOS), define quintessential EC-specific physiologic functions. It is not clear whether long noncoding RNAs (lncRNAs) also define cardiovascular cell type-specific phenotypes, especially in the vascular endothelium. Here, we report the existence of a set of EC-enriched lncRNAs and define a role for pliced- ranscript ndothelial- nriched lncRNA (STEEL) in angiogenic potential, macrovascular/microvascular identity, and shear stress responsiveness. STEEL is expressed from the terminus of the HOXD locus and is transcribed antisense to HOXD transcription factors. STEEL RNA increases the number and integrity of de novo perfused microvessels in an in vivo model and augments angiogenesis in vitro. The STEEL RNA is polyadenylated, nuclear enriched, and has microvascular predominance. Functionally, STEEL regulates a number of genes in diverse ECs. Of interest, STEEL up-regulates both eNOS and the transcription factor Kruppel-like factor 2 (KLF2), and is subject to feedback inhibition by both eNOS and shear-augmented KLF2. Mechanistically, STEEL up-regulation of eNOS and KLF2 is transcriptionally mediated, in part, via interaction of chromatin-associated STEEL with the poly-ADP ribosylase, PARP1. For instance, STEEL recruits PARP1 to the KLF2 promoter. This work identifies a role for EC-enriched lncRNAs in the phenotypic adaptation of ECs to both body position and hemodynamic forces and establishes a newer role for lncRNAs in the transcriptional regulation of EC identity.